2006
DOI: 10.1080/17453670610046019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ACL and ACL graft forces before and after ACL reconstruction an in-vitro robotic investigation

Abstract: Background Long-term follow-up studies have indicated that there is an increased incidence of arthrosis following anterior cruciate ligament (ACL) reconstruction, suggesting that the reconstruction may not reproduce intact ACL biomechanics. We studied not only the magnitude but also the orientation of the ACL and ACL graft forces.Methods 10 knee specimens were tested on a robotic testing system with the ACL intact, deficient, and reconstructed (using a bone-patella tendon-bone graft). The magnitude and orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…In addition, a graft placed too far anteriorly could result in a vertically oriented graft [5,9,16,25,29,56]. A vertically oriented graft is unlikely to restore the oblique orientation of the ACL [9,32,44,54] and might provide inadequate restraint to the increased internal rotation [4,12,17] and medial tibial translation [12,31] observed in patients with ACL deficiency. Altered kinematics after ACL injury are thought to predispose the knee to degenerative changes [4,17,39,40,50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a graft placed too far anteriorly could result in a vertically oriented graft [5,9,16,25,29,56]. A vertically oriented graft is unlikely to restore the oblique orientation of the ACL [9,32,44,54] and might provide inadequate restraint to the increased internal rotation [4,12,17] and medial tibial translation [12,31] observed in patients with ACL deficiency. Altered kinematics after ACL injury are thought to predispose the knee to degenerative changes [4,17,39,40,50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies demonstrated that ACL provides resistance to lateral translation. 36,37 In ACL deficient knees, a lateral shift of the femur occurs relative to normal knees. 36,37 The constraining function of the ACL was lost in our PCR-TKAs, which might have caused the lateral femoral translation.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to incorporate joint structural contributions to resultant 3D joint and ligament load states may also lead to erroneous interpretations of injury risk via a sagittal loading mecha nism. A large posterior tibial slope for example, viewed to occur more frequently in women (Brandon et al, 2006), will likely promote increases in anteriorly directed tibial loads, and further orient the ACL such that a greater portion of this load is transferred along the ligament (Li et al, 2006;Petersen and Zantop, 2007). Expanding cur rent models to incorporate an anatomically relevant knee joint (Pflum et al, 2004;Shelburne et al, 2004) capable of accommodating subject-based variations in knee anato mies and laxities would provide immediate insights into individual predispositions to ACL injury based on joint and tissue biomechanical vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%